HYPOMAGNESEMIA A COFACTOR FOR ATHEROGENESIS IN NON INSULIN DEPENDENT DIABETES MELLITUS - V.ARUNA M.D.; K.AMBIKADEVI M.D. (International Journal of Pharma and Bio Sciences, 2014)
To investigate correlation between Hypomagnesemia and biochemical parameters of atherosclerosis in NIDDM 2.To investigate correlation between serum “C”-peptide levels and glycemic control as evaluated by HbA1c.ASRAM college of Medical Sciences & ASRAM Hospital outpatients and inpatients, Eluru,AP .76 patients of Type II Diabetes Mellitus(NIDDM) aged above 40yrs & 30 number of age & sex matched healthy controls.Serum C-peptide was measured by Direct chemiluminiscence. Fasting Blood Glucose, HbA1c, Serum Total Cholesterol, HDL-C,and Serum Magnesium were considered for analysis and measured using standardized kits from ‘Coral clinical systems’.The optical density readings taken in a photoelectric colorimeter.Patients with Hypomagnesemia defined as serum Mg++ <1.6 mg/dl were compared with those having normal serum Mg++ levels (1.6-3.0mg/dl).In the present study inverse relation observed between glycemic control and serum Magnesium levels P-<0.0034.The serum C-Peptide levels showed greater variance in hypomagnesemic diabetic patients compared to normomagnesemic diabetic patients (P <0.012).Strong correlation observed between serum C-Peptide levels and glycemic control with reduced C-Peptide levels in diabetic patients with poor glycemic control (>8%). P<0.00001,The presence of associated complications in diabetic patients showed reduced C-peptide levels,(P-value <0.00001).ANOVA between controls and diabetic patients with hypomagnesemia showed significantly elevated TC/HDLC ratio in diabetic patients with hypomagnesemia (P-<0.026).The present study concluded with the principal observation that glycemic control and reduced C-Peptide levels influenced hypomagnesemia.Deleterious effects of dyslipidemia of Diabetes Mellitus per se were exacerbated by hypomagnesemia and reduced C-Peptide levels.